SYNDROMES OF NARCOLEPSY AND MENINGOENCEPHALITIS IN THE EARLY STAGE OF KAWASAKI DISEASE (CLINICAL CASES) - V. V. Shprakh (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
The article presents the description of the clinical follow-up of two children of 4 and 6 years with Kawasaki disease who along with cardiac complications had symptoms of the nervous system damage in the form of the syndrome of narcolepsy and meningoencephalitis. While conducting MRI-angiography of the brain of patient with the syndrome ofnarcolepsy the signs of vasculitis of siphon internal carotid arteries on both sides were discovered. While conducting MSCT of the brain of the child with the meningoencephalitis syndrome the signs of vascular encephalopathy were found. A significant regression of neurological symptoms was observed during the treatment in both children. These cases are interesting because the symptoms of the nervous system damage along with cardiac complications were significantly expressed and the diagnosis of cerebral vasculitis was confirmed by neuroimaging. Cases of the nervous system damage at Kawasaki disease are rare, the literature has little data about the neurological syndromes in this disease, that requires further research in this direction.